Patterns of Metacognitive Levels in Chemistry Problem-posing - Benny Yodi Sawuwu (SEAMEO QITEP in Science, 2024)
This study aims to describe the patterns of metacognitive levels in chemistry problem-posing activity of 76 undergraduate students from the Chemistry Education Department of Yogyakarta State University. Chemistry articles used in this investigation and the chemistry problems were classified based on the taxonomy of chemistry problem-posing skills where problems were later classified into seven metacognitive levels. Semiotic analysis was conducted to find the meaning of the signs found in the chemistry problems. This data analysis used and modified the three steps of the semiotic analysis with a phenomenological reduction method. Chemistry problem-posing in this current study shows the flow of the formulation for each problem. The input aspect for the formulation determines the process and the output result. The seven patterns are sorted into four participant types in submitting the chemistry problems: planning error (for poor, fair, and low intermediate level), evaluation error (for intermediate level), the imbalance metacognitive (for high intermediate and excellent level), and balance metacognitive (for outstanding level). The higher the level, the more complex and multiperspective determinations used for arranging a chemistry problem.